2023
DOI: 10.1002/jcsm.13208
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of IL‐12/23 neutralizing antibody in sarcopenia associated with dextran sulfate sodium‐induced experimental colitis

Abstract: Background The improvement of colitis symptoms by treatment with IL‐12/23 p40 neutralizing antibody should increase the muscle mass and the function of the sarcopenia phenotype. Methods An experimental colitis model was induced by oral administration of 2% dextran sulfate sodium (DSS) for 7 days. During induction of colitis, IL‐12/23 p40 neutralizing antibody was injected twice on Days 3 and 5. The total body mass index was measured by dual‐energy X‐ray absorptiometry. The muscle function was measured by forel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, Jung et al indicated that lower inhibition of IL-12/23 was a protective role for muscle atrophy in the colitis-induced trial. The association between the circulating cytokines and sarcopenia remains controversial, and the demographic differences contribute to this difference in conclusions (62). Thus, more large-sample studies need to be conducted to further validate the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…However, Jung et al indicated that lower inhibition of IL-12/23 was a protective role for muscle atrophy in the colitis-induced trial. The association between the circulating cytokines and sarcopenia remains controversial, and the demographic differences contribute to this difference in conclusions (62). Thus, more large-sample studies need to be conducted to further validate the relationship.…”
Section: Discussionmentioning
confidence: 99%